"Awful Gladness": The Dual Political Rhetorics of Du Bois's "Of the Passing of the First-Born". (February 2019) - Menzel, Annie
W.E.B. Du Bois's elegy for his infant son, "Of the Passing of the First-Born, " in The Souls of Black Folk, has received relatively scant attention from political theorists. Yet it illuminates crucial developments in Du Bois's political thought. It memorializes a tragedy central to his turn from scientific facts to rhetorical appeals to emotion. Its rhetoric also exemplifies a broader tension in his writings, between masculinist and elitist commitments and more insurrectionary impulses. In its normalizing rhetorical mode, which dominates, the elegy depicts an idealized patriarchal bourgeois household—potentially eliciting white readers' sympathetic identification, but failing to displace the gendered and classed logic of racial exclusion. Its moments of transgressive rhetoric complicate or refuse such identification, celebrating Burghardt's racial impurity and invoking a lineage of black maternal ambivalence. Though each is vexed and ephemeral, these moments of transgressive rhetoric reveal countervailing impulses that Du Bois would articulate in later writings.